Production of donor-derived offspring by allogeneic transplantation of spermatogonia in Chinese rosy bitterling†. Issue 4 (15th November 2018) - Octavera, Anna; Yoshizaki, Goro
Abstract: Many bitterling species are facing extinction because of habitat destruction. Since cryopreservation of fish eggs is still not available to date due to their large size and high yolk content, long-term and stable storage of bitterling genetic resources is currently not possible. We recently discovered that cryopreservation of early-stage germ cells is possible in several fish species and that functional gametes derived from the frozen materials can be produced through their transplantation to embryonic recipients. However, bitterlings have uniquely shaped eggs and their embryos are extremely fragile, making it difficult to perform germ cell transplantation. Therefore, as a first step, we conducted intra-species spermatogonial transplantation using recessive albino Chinese rosy bitterling as donors and wild-type Chinese rosy bitterling as recipients to develop a system to convert freezable early-stage germ cells into functional gametes, particularly eggs. Approximately 3000 testicular cells were transplanted into the peritoneal cavity of 4-day-old germ cell-less recipient embryos produced by dead end ( dnd) -knockdown. At 6 months, ten male recipients and nine female recipients produced gametes. Mating studies with the opposite sex of recessive albino control fish revealed that six males and three females produced only albino offspring, suggesting that these recipients' endogenous germ cells were completely removed by dnd -knockdown and they produced only donor-derived gametes. Thus, we successfully established a germ cell transplantation system in an iconic endangered teleost, bitterling. The technology established in this study can be directly applied to produce functional gametes of endangered bitterlings using cryopreserved donor cells. Abstract : Allogeneic germ cell transplantation system was established using germ cell-less embryonic recipients produced by dead end -knockdown in a bitterling, which is an iconic endangered fish species.